PENGARUH PENERAPAN STRUKTUR ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN (STUDI KASUS PADA PT CITRACITI PACIFIC PEKANBARU) - ", Nuraini; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aim to analyze positive and significant of implementationorganization structure unfluence work satisfaction at PT Citraciti PacificPekanbaru. This reseacrh used simple linear regression analisis by means SPSS16 program. The result show that the implementation of organization structuredimension consisting of complexity, formalization, centralization –decentralization together effect on work satisfaction at PT Citraciti PacificPekanbaru. Dimension implementation of organization structure to contribute towork satisfaction variable of 0,260 or 26% while the remaining 74% iscontributed by other variables not included in this study. Dependen variable canbe choosed with similarity research object of corporate organization situation.Keywords : Implementation, Organization structure, working satisfaction